Waste to energy and circular economy: the case of anaerobic digestion. Issue 4 (19th June 2020) - Hussain, Zahid; Mishra, Jyoti; Vanacore, Emanuela
Abstract : Purpose: This paper highlights how biological waste materials can be used for generating the much needed energy and obtaining nutrient-rich compost for agriculture through anaerobic digestion (AD). The paper further highlights the importance of small and medium enterprises (SMEs) in using AD for converting waste to energy (WTE), leading to many environmental benefits as well as clean energy generation. It would help to reduce pollution, water acidification and carbon emissions that eventually lead to climate change. Design/methodology/approach: The researchers undertook an in-depth study to highlight the role played by an SME in converting WTE and helping towards achieving circularity. An exploratory case-based approach was used to understand value leakage for an AD plant operating on WTE principles in the UK. The plant is still currently active, and it is located in the Midlands, England. Fifteen semi-structured interviews were undertaken with different stakeholders. Findings: This paper reveals the importance of WTE and the significant role played by AD in converting food waste into useful matter. It reports further into the value leakage issue faced in the AD plants. It demonstrates the importance of technological innovation in SME to capture value leakages in a circular model. Most importantly, it demonstrates how SMEs gain competitive advantage and generate value proposition, while they aim for zero waste to landfill objective. Research limitations/implications: The research involves a case study based on an SME, operating on a circular business model. It will be worth investigating how other businesses could gain competitive advantage. For SMEs interested in AD for WTE, this paper introduces further technological innovation to the AD process to leverage further potential for reuse of waste liquid. Any SMEs entering WTE market ought to take into consideration such design implications. Practical implications: The paper reveals how the use of waste by SMEs would lead to many environmental benefits as well as clean energy generation. It would help to reduce pollution, water acidification and carbon emissions that eventually lead to climate change. It is useful for addressing the needs of waste food producers and is a cheap raw material for generating energy. The benefits to the public are that it reduces the need for landfill and increases recycling. Social implications: The WTE is an effective way of making use of last-stage waste. Originality/value: Despite SMEs being the powerhouse of the European economies, there is limited research investigating how circular economy (CE) could unlock their potential. Moreover, development of AD in the UK has lagged behind other EU countries. We highlight value leakages and argue how technological innovation should be used to close the value chain loop in the WTE production process. This paper, therefore, demonstrates the important role of an AD process, which involves decomposition of biodegradable materials. It shows that AD is an economically viable and environmentally friendly process of obtaining clean energy at low cost.